PREDICTION OF THE UNEMPLOYMENT RATE IN MALAYSIA - Suraya Fadilah Ramli; Muhammad Firdaus; Hazmi Uzair; Amirul Zharif (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Unemployment is a global phenomenon which is considered as an issue around the world. Generally, voluntary unemployment happens when an individual leaves their current job in order to find another while involuntary unemployment occurs as an individual is dismissed from their job and needs to find a new one. The objective of this paper contains three consequent parts, which are to identify the significant factors that affect the unemployment rate in Malaysia. Besides that, it is to find the best models for forecasting the unemployment rate in Malaysia. Lastly, to forecast the future value of the unemployment rate in Malaysia using the best model. The scope of this study is surrounding entire Malaysia. The variables selected for the study are inflation rate, numbers of population and gross domestic product (GDP). In order to analyze the factors, the significance level is tested while forecasting the unemployment rate requires the ARIMA and Holt’s exponential smoothing methods. The results of the regression analysis show that the significant factors of unemployment are the inflation rate and population. The optimal model to forecast the unemployment rate in Malaysia is ARIMA (2,1,2). The research proved that there was an increment in the unemployment rate in Malaysia. Implying that the value of the unemployment rate in Malaysia will slightly increase from the year 2017 until 2026 and it predicts the future value of the unemployment rate in Malaysia is stable and not considered as the critical problem within the next ten years.